I can't get no Sleep: The Role of Leaders' Health and Leadership Behavior on Employees' Sleep Quality. Issue 6 (2nd November 2022) - Matick, Eva; Kottwitz, Maria U.; Rigotti, Thomas; Otto, Kathleen
ABSTRACT: A leader's role is often associated with increased psychosocial demands, which could lead to rumination during nonwork time. Leader rumination might trigger a cascade of mechanisms causing employee rumination and eventually persistent employee sleep problems. In a three-wave study, we examined whether leader rumination predicts changes in employee sleep quality linked by employee rumination. As a possible serial mechanism underlying the trickle-down effect of leader rumination on employee rumination, we investigated leaders' general health and resource-oriented leadership behaviour. Based on self-report data from 94 leaders and their 332 employees, we found support for a multilevel mediation model in which leader rumination negatively affected employee sleep quality via employee rumination while controlling for baseline measures and a shared work environment (workload). Finally, leader rumination was negatively related to employee sleep quality via the serial mediation of leader health, resource-oriented leadership, and rumination perceived by the team members. The results demonstrate the importance of leader rumination for employees' sleep quality nearly 2 years later and provide knowledge that can be used to expand and optimize interventions.